Integral identities based on symmetric and skew-symmetric weight functions for a semi-infinite interfacial crack in anisotropic magnetoelectroelastic bimaterials. (15th June 2016) - Ma, P.; Su, R.K.L.; Feng, W.J.
Abstract: In this paper, we address a semi-infinite interfacial crack problem in an anisotropic magnetoelectroelastic (MEE) bimaterial system subjected to a magnetoelectromechanical asymmetric load on the crack surface. First, the symmetric and skew-symmetric weight functions are derived for a two-dimensional (2-D) deformation problem. Using these weight functions and extending the Betti formula to MEE materials, the integral identities are further obtained and the present crack problem is formulated in terms of singular integral equations, which establish the relationship between the applied external load and the generalized displacement jump across the crack faces. The illustrative examples in relation to Mode III, and Mode I and Mode II problems show that the method developed in this study avoids the use of Green's function and is very convenient for the fracture analysis of MEE solids, in which a multi-field coupled effect is observed.